OPTIMIZATION OF ?-AMYLASE PRODUCTION IN SOLID SUBSTRATE FERMENTATION - Tanyildizi, M. Saban; Selen, Veyis; Ozer, Dursun (John Wiley & Sons Inc, 2009)
Response surface methodology (RSM) was used to optimize the medium components of alpha-amylase production using solid Substrate fermentation (SSF). Hazelnut cake (HC), peptone, yeast extract (YE), and (NH(4))(2)SO(4) were selected as independent variables for optimization. Central composite design (CCD) was used in design experiments and analysis results. This procedure limited the number of actual experiments performed while allowing possible interactions between the independent variables. By using CCD, 30 experiments were performed for determining the interaction of independent variables and optimization of fermentation medium. The P-value of the coefficient of linear effect of (NH(4))(2)SO(4) concentrations, which was obtained as 0.0001 has shown that this parameter has the greatest effect on the production of alpha-amylase. Model F-value (5.62) implies that the model is significant. The highest alpha-amylase activity (4895 IU) was measured when the HC, peptone, YE, and (NH(4))(2)SO(4) concentrations in the medium were 22.62, 5.20, 1.62, and 6.81 gL(-1), respectively.
Keywords: alpha-amylase; solid Substrate fermentation; hazelnut cake; response surface methodology